Validation and Practicality Test of Grammar Cards Website for 10th Grade Students - Safhira Fauzia Ramadhanti; Rona Elfiza; Gatot Subroto (Universitas Maritim Raja Ali Haji (UMRAH), 2023)
The students face some difficulties in the English course, especially in learning grammar. Their grammar mastery is low and there are no instructional media specifically used for learning grammar in the English class for online and offline sessions. This research aims to determine the validation and test the feasibility of Grammar Cards Website as instructional media for learning grammar in English course. The participants of this research are 22 students of X MIPA 3 in SMAN 5 Tanjungpinang. The design of this research is qualitative. The process in qualitative data is collected from validation sheets and the practicality test questionnaire. The result of the study shows that Grammar Cards Website is valid and feasible to be used as instructional media in English grammar learning for 10th grade students. Grammar Cards Website instructional media is easy, attractive, and useful.